Modal Sosial Kelompok dalam Pengembangan Ekowisata Mangrove di Desa Kayu Ara Permai Kecamatan Sungai Apit Kabupaten Siak - Fifi Alfiah; Rina Susanti (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2023)
Social capital that has roles and responsibilities in determining ecotourism development. This study aims to look at the elements of social capital of the Konservasi Laskar Mandiri Group in the Development of Mangrove Sungai Bersejarah Ecotourism. The research was conducted using qualitative research methods and the data research techniques used included in-depth interview, observation and documentation. The subjects of study were selected using a purposive sampling technique with a total of 5 group members who were active and had joined the group for more than 2 years and 1 key informant, namely the village apparatus of Kayu Ara Permai. The research found some social capital elements in groups: networks, beliefs, norms and pro-active actions that are intertwined between group memberships, communities and partners. Social Capital contained in the group plays a role as an adhesive (Bonding) among members to foster high awareness, a sense of comfort, safety, shared responsibility, and gain good knowledge on how to increase group capacity, develop ecotourism and process the mangrove derivative products. The role of bridging (Bridging) encourages positive behavior, increases community participation, as well as funding and makes Ecotourism a village development priority. Finally, the role of liaison (Linking) is the establishment of cooperation with different strata to obtain funds from partners to build ecotourism facilities, increase group knowledge and promote ecotourism and process the mangrove derivative products produced by the group.